FasL is a catabolic factor in alveolar bone homeostasis - Apaza Alccayhuaman, Karol Alí; Heimel, Patrick; Lee, Jung Seok; Tangl, Stefan; Kuchler, Ulrike; Marchesan, Julie; Panahipour, Layla; Lettner, Stefan; Matalová, Eva; Gruber, Reinhard (Journal of clinical periodontology, 2023)
AIM: Fas ligand (FasL) belongs to the tumour necrosis factor superfamily regulating bone turnover, inflammation, and apoptosis. The appendicular and axial skeleton phenotype of mature Faslgld mice has been reported. The impact of FasL on the alveolar bone providing support for the teeth at mature stages under healthy and induced inflammatory conditions remains unknown. MATERIALS AND METHODS: We performed a phenotypical analysis of mice carrying the homozygous Faslgld mutation and wild-type (WT) mice (C57BL/6) under healthy conditions and upon ligature-induced periodontitis. After 12 days, micro-computed tomography analysis revealed the distance between the cement enamel junction and the alveolar bone crest. Additional structural parameters, such as the bone volume fraction (BV/TV) and the periodontal ligament space volume, were measured. Histological analyses were performed to visualize the catabolic changes at the defect site. RESULTS: Healthy Faslgld mice were found to have more periodontal bone than their WT littermates. Faslgld had no significant effect on inflammatory osteolysis compared to WT controls with ligatures. Histology revealed eroded surfaces at the root and in the inter-proximal bone in both strains. CONCLUSIONS: Our findings suggest that FasL is a catabolic factor in alveolar bone homeostasis but it does not affect the inflammatory osteolysis.
Keywords: myši; periodontitis; Homeostasis; ligand Fas; Mice; Animals; myši inbrední C57BL; osteolysis; zvířata; X-Ray Microtomography; rentgenová mikrotomografie; Mice, Inbred C57BL; gld; FasL; osteolýza; Fas Ligand Protein; homeostáza; ligature; Osteolysis